Mediating national identity through relational spirituality: a framework from christian education in indigenous contexts - Jolanti Wisje Pentury; Yakob Godlif Malatuny; Marlisa Sarwuna (Lentera Negeri, 2026)
Nationalism education in Papua as a complex issue shaped by Christianity, Indigenous Papuan identity, multicultural interaction, historical memory, social injustice, and Indonesian citizenship. Methodologically, it uses a qualitative phenomenological design with 15 CRE teachers and 50 Indigenous Papuan students from 7 schools, selected through purposive criterion sampling, with interviews, classroom observations, and document analysis validated through triangulation, member checking, reflexive bracketing, and an audit trail. The results show that CRE supports inclusive nationalism by translating Christian values such as love, justice, care, reconciliation, and respect for human dignity into concrete social practices. Students understood nationalism through lived experiences of solidarity, mutual cooperation, respect for diversity, and awareness of social justice. The article concludes that CRE can mediate Papuan identity and Indonesian citizenship integratively, and it contributes the concept of relational spirituality-based nationalism as a framework for multicultural and humanistic education in Papua.